On Twisted Tensor Product Group Embeddings and the Spin Representation of Symplectic Groups: The Case q Odd. (5th June 2011) - Cossidente, Antonio
Abstract : The groupP S p 8 ( q ), q odd, has a maximal subgroup isomorphic to3. P S p 2 ( q 3 ) belonging to the Aschbacher class𝒞 9 . It is the full stabilizer of a complete partial ovoid and of a complete partial 3-spread of𝒲 7 ( q ) .